2018
DOI: 10.1038/s41372-018-0209-5
|View full text |Cite
|
Sign up to set email alerts
|

Preterm neuroimaging and neurodevelopmental outcome: a focus on intraventricular hemorrhage, post-hemorrhagic hydrocephalus, and associated brain injury

Abstract: Intraventricular hemorrhage in the setting of prematurity remains the most common cause of acquired hydrocephalus. Neonates with progressive post-hemorrhagic hydrocephalus are at risk for adverse neurodevelopmental outcomes. The goal of this review is to describe the distinct and often overlapping types of brain injury in the preterm neonate, with a focus on neonatal hydrocephalus, and to connect injury on imaging to neurodevelopmental outcome risk. Head ultrasound and magnetic resonance imaging findings are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 105 publications
0
52
0
2
Order By: Relevance
“…Brain imaging is essential in neonatal neuropediatric diagnostics [1]. In neonates, magnetic resonance imaging (MRI) serves as a reliable modality for the detection of brain pathologies, as well as for the assessment of myelination [2][3][4][5][6]. Based on conventional MRI findings, substantial information about the future course of neurodevelopment can be obtained [2,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain imaging is essential in neonatal neuropediatric diagnostics [1]. In neonates, magnetic resonance imaging (MRI) serves as a reliable modality for the detection of brain pathologies, as well as for the assessment of myelination [2][3][4][5][6]. Based on conventional MRI findings, substantial information about the future course of neurodevelopment can be obtained [2,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In neonates, magnetic resonance imaging (MRI) serves as a reliable modality for the detection of brain pathologies, as well as for the assessment of myelination [2][3][4][5][6]. Based on conventional MRI findings, substantial information about the future course of neurodevelopment can be obtained [2,[7][8][9]. Apart from deficient myelination, brain injury, e.g., due to hemorrhage, asphyxia, or infarction during the prenatal and neonatal period, may severely impair brain maturation [6,8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventricular dilation is a frequent phenomenon in patients with TBI and can present in follow-up examinations and develop into post-traumatic hydrocephalus (PTH) (44). Various studies have indicated that SAH and intraventricular haemorrhage (IVH) may be associated with hydrocephalus development following TBI, which can result in acute ventricular dilation at 24 h following TBI (45,46). As a result of the tearing of subependymal veins that line ventricular cavities, IVH has been associated with severe injuries (47).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criteria of pregnancy, perinatal and neonatal co-morbidities and complications are presented in additional le 1 [23][24][25][26][27][28][29][30][31][32][33][34]. De nitions regarding vital statistics are based on the original survey [11,20], and the 10 th revision of the international classi cation of diseases [35].…”
Section: De Nitions Of Preterm Morbidity and Mortalitymentioning
confidence: 99%